Effect of PAR-2 Deficiency in Mice on KC Expression after Intratracheal LPS Administration. (29th September 2011) - Williams, Julie C.; Lee, Rebecca D.; Doerschuk, Claire M.; Mackman, Nigel
Abstract : Protease activated receptors (PAR) have been shown to play a role in inflammation. PAR-2 is expressed by numerous cells in the lung and has either proinflammatory, anti-inflammatory, or no effect depending on the model. Here, we examined the role of PAR-2 in a model of LPS-induced lung inflammation. We found that PAR-2-deficient mice had significantly less KC expression in bronchial lavage fluid compared with wild-type mice but there was no difference in MIP-2 or TNF- α expression. We also found that isolated alveolar and resident peritoneal macrophages lacking PAR-2 showed a similar deficit in KC after LPS stimulation without differences in MIP-2 or TNF- α . Infiltration of neutrophils and macrophages into the lung following LPS administration was not affected by an absence of PAR-2. Our results support the notion that PAR-2 plays a role in LPS activation of TLR4 signaling in macrophages.